‘Sasanian’ silver plate from al-Ṣabāḥ Collection in light of aesthetic features of Sasanian toreutics - SKUPNIEWICZ, Patryk (Historia i Świat, 2019)
Recently published silver plate from al-Sabah Collection, of unknown provenance, has been firmly attributed as Sasanian. In fact, technically, it is related to the Sasanian silverwork however aesthetic examination allows to raise the doubts whether it is genuine. The plate must be compared not only with central-Sasanian artworks but all ancient ‘Oriental silver’, including pieces attributed as Hephtalite or Sogdian. The design of the plate does not have any relation with any of the known examples of late antique oriental toreutics. Central scene of heroic combat with powerful beast or beasts has never been surrounded with the ring containing other hunting scenes is unknown as well. The disbalanced decorum is even more clear when we remind that the central scene shows hunting on foot and the marginal ones – mounted. The details of fixed aesthetic elements – position of personages, beasts, weapons do not belong to Sasanian canon. The unique nature of the plate might result from many factors but the combination of unknown provenance and lack of relation to legitimate Sasanian canon require utmost cautiousness towards the object.